The Role of Tectonic Plate Thickness and Mantle Conductance in Determining Regional Vulnerability to Extreme Space Weather Events: Possible Enhancement of Magnetic Source Fields by Secondary Induction in the Asthenosphere - Fiona Simpson; Karsten Bahr (Space Weather)
Abstract During magnetic storms, solar‐magnetosphere‐ionosphere‐Earth interactions give rise to geomagnetically induced currents (GICs) in man‐made technological conductors such as power grids, gas pipelines, and railway networks with potentially damaging outcomes. Generally, electrically conductive regions of the Earth are assumed to be less at risk to GICs than resistive ones, since induced electric fields associated with GICs are linearly related to given magnetic source fields via Earth's impedance. Here, we show that magnetic source fields associated with storms can be enhanced by secondary electromagnetic (EM) induction in Earth's electrically conductive asthenosphere and that this previously neglected effect can give rise to larger electric fields close to the lithosphere‐asthenosphere boundary in regions where the conductance of the asthenosphere is higher. Our analysis of data from the 30 October 2003 “Halloween” and 8 September 2017 storms shows that the magnitudes of electric fields from both storms are affected by lithospheric plate thickness and asthenosphere conductance (conductivity‐thickness product) and that they are 5 times larger in southern Sweden (>5 V/km for the 30 October 2003 “Halloween” storm) than in central Scotland. Our results provide insight into why Sweden experienced a storm‐related power outage in 2003, whereas Scotland did not.